Synthetic Antiferromagnets: Optically Inspired Nanomagnonics with Nonreciprocal Spin Waves in Synthetic Antiferromagnets (Adv. Mater. 9/2020). Issue 9 (3rd March 2020) - Albisetti, Edoardo; Tacchi, Silvia; Silvani, Raffaele; Scaramuzzi, Giuseppe; Finizio, Simone; Wintz, Sebastian; Rinaldi, Christian; Cantoni, Matteo; Raabe, Jörg; Carlotti, Giovanni; Bertacco, Riccardo; Riedo, Elisa; et al.
Abstract : Spin‐waves, propagating perturbations in the spin arrangement of magnetic materials, are promising candidates for low‐power computation and signal processing. In article number 1906439, Edoardo Albisetti, Elisa Riedo, Daniela Petti, and co‐workers demonstrate an optically inspired nanomagnonic platform using nanopatterned spin‐textures for launching spatially shaped wavefronts and generating multi‐beam interference patterns. They show that controlling spin‐waves in synthetic antiferromagnets makes a fundamental step toward optically inspired spin‐wave processing.